Arabic (Islamized) Medicine and its Culture in Early French Renaissance - Angrini, Mahmud; Nasser Kaadan, Abdul (Universitas Darussalam Gontor, 2025)
This paper explores the impact of Islamised Arabic medicine on early Renaissance France, particularly in the south. Following Muslim conquests in Western Europe, including Sardinia, Corsica, and Al-Andalus, their presence reached Narbonne in 720 CE and faced a turning point at the Battle of Tours in 732 CE. Despite military defeat, Muslim intellectual influence endured, especially in Montpellier, where exiled scholars helped shape a major centre of medical education. The University of Montpellier became crucial in transmitting Arabic medical knowledge to Europe. This study contends that medicine was a vital, yet often overlooked, channel for Islamic knowledge to shape early French Renaissance thought.